2002
DOI: 10.1084/jem.20020263
|View full text |Cite
|
Sign up to set email alerts
|

Opsonization of Apoptotic Cells by Autologous iC3b Facilitates Clearance by Immature Dendritic Cells, Down-regulates DR and CD86, and Up-regulates CC Chemokine Receptor 7

Abstract: Immature dendritic cells (iDCs) do not mature after uptake of apoptotic cells and may play a role in the induction of peripheral tolerance to self antigens derived from apoptotic material. The integrins, αvβ3, αvβ5, and the scavenger receptor, CD36, have been shown to mediate uptake of apoptotic cells by iDCs. However, it is not known whether the complement system, also takes part in this process. In this study we investigated the ability of iDCs to bind to apoptotic cells opsonized by iC3b. Monocyte-derived d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
236
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(252 citation statements)
references
References 48 publications
(61 reference statements)
12
236
1
3
Order By: Relevance
“…The suppression of proinflammatory cytokines induced by CR3 on DCs may be beneficial in these cases. CR3 triggering is often obtained using particulated systems such as RBC opsonized with iC3b (6,8). The ability to induce CR3 inhibitory effects using direct ligation via mAbs, as we achieved, is encouraging for its ready feasibility in testing this approach therapeutically.…”
Section: Discussionmentioning
confidence: 90%
“…The suppression of proinflammatory cytokines induced by CR3 on DCs may be beneficial in these cases. CR3 triggering is often obtained using particulated systems such as RBC opsonized with iC3b (6,8). The ability to induce CR3 inhibitory effects using direct ligation via mAbs, as we achieved, is encouraging for its ready feasibility in testing this approach therapeutically.…”
Section: Discussionmentioning
confidence: 90%
“…Again microparticles were at least as effective as apoptotic cells. In this context, it is of interest that a reduced expression of MHC class II and CD86 has also been described with dendritic cells that were exposed to iC3b-coated apoptotic cells [29].…”
Section: Discussionmentioning
confidence: 98%
“…Microparticles exposed to serum are able to activate complement, resulting in a deposition of iC3b on their surface. It has previously been shown for apoptotic cells that complement activation plays an important role for their uptake by macrophages and immature dendritic cells [27][28][29]. Phosphatidylserine on apoptotic cells is at least partially involved in the activation of complement and contributes to the deposition of complement components like iC3b on the membrane surface [27,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of apoptosis in the induction or prevention of an immune response is still unclear. Indeed, some groups have demonstrated that the uptake of apoptotic cells by DC results in T cell tolerance [4][5][6]. Conversely, other groups have shown that DC that have phagocytosed apoptotic bodies from virus-infected cells can present viral antigens to cytotoxic T cells and induce a cytotoxic response [7,8].…”
Section: Introductionmentioning
confidence: 99%